A veiculação da ciência nas capas de revistas: o caso da revista Galileu - Lacombe, Michel da Silva Coelho (Universidade Federal de São Carlos, 2012)
The objective of this study is to analyze the scientific dissemination in the magazine Galileu. Through a presentation of the configuration of the journalistic practice and theoretical frameworks Discourse Analysis affiliated with the French line, I intend to discuss how the relationship is established and textual imagery on the cover of the publication in order to present what is the effect desired by the player : to present the scientific production or sell the number. To complement the research, I intend to present, based on a section of the same magazine, composed of articles written, who the characters are presented and what is, in fact, the relevance of these within the scope of science.
Keywords: Desenvolvimento social ciência, tecnologia e sociedade; Análise do discurso; Jornalismo; Divulgação Científica; Science, Technology and Society; Journalism; Science Communication; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO